混合驱动凸轮连杆机械压力机的分析与仿真 - 李竞洋; 葛正浩; 苏鹏刚; 蒋萌 (Jixie chuandong)
The significance of applying hybrid cam-linkage mechanism to mechanical press is expounded.This new type of mechanistic configuration for the hybrid cam-linkage mechanical press is proposed and its kinematic principle is analyzed.Using complex number vector method,the inverse kinematic analysis of this hybrid mechanism is carried out and the actual operating function that can meet the demand of processing techniques is worked out.Based on Pro/Mechanism,The mechanism motion simulation is done.The results show that the hybrid cam-linkage mechanical press can realize multiple motion specification and satisfy multi-technique request from slider velocity characteristics in the course of process.According to the structure analysis and simulation for hybrid seven-bar mechanism,the conclusion that compared to the hybrid seven-bar press,the hybrid cam-linkage press has the merits of easy link lengths restriction and good motion output is obtained.At last,the dynamic simulation model is designed,and the power distribution of the constant speed motor and the servo-motor is analyzed.